Ceftazidime-avibactam use selects multidrug-resistance and prevents designing collateral sensitivity-based therapies against Pseudomonas aeruginosa - Sara Hernando-Amado; María A. Gomis-Font; José R. Valverde; Antonio Oliver; José Luis Martínez (Nature Communications)
Abstract Ceftazidime-avibactam is a β-lactam/β-lactamase inhibitor combination restricted for the treatment of multidrug-resistant infections of Pseudomonas aeruginosa non-susceptible to ceftazidime and resistant to carbapenems. Crucially, it has not been studied if its use could allow the design or application of new or stablished evolution-based strategies that exploit the increased susceptibility that emerges when resistance is acquired (collateral sensitivity, CS). Works in the field have focused on the study of CS in model strains, but to be exploited it must robustly emerge in pre-existing resistant mutants that can coexist in a patient. This is the first analysis of CS robustness on this last-resort drug. We evolved 15 clinical isolates on ceftazidime-avibactam and in absence of inhibitor, and here we show that we found no robust -exploitable- pattern of CS. This, together with the selection of cross-resistance and the impossibility of using previously described CS-based strategies, supports that avibactam should be restricted for the treatment of particular genotypes.